Precision measurement of the Ξ0 mass and the branching ratios of the decays Ξ0 → Λγ and Ξ0 → ∑0γ - Fanti, V; Lai, A; Marras, D; Musa, L; Nappi, A; Hay, B; Moore, K; Moore, R; Munday, D; Needham, MD; Parker, M; White, T; et al. (2000)
A new precision measurement of the Ξ0 mass has been performed at the NA48 experiment at the CERN SPS. The value obtained is [1314.82±0.06 (stat.) ±0.2 (syst.)] MeV/c2. The branching ratios of Xi;0 radiative decays have been measured as: Br(Ξ0 → Λγ) = [1.90 ± 0.34(stat.) ± 0.19(syst.)] · 10-3 and Br(Ξ0 → ∑0γ) = [3.14 ± 0.76(stat.) ± 0.32(syst.)] · 10-3.